„Forradalmi” változások a menedzsment területén - Nádasdi, Ferenc; Keszi-Szeremlei , Andrea (International Journal of Engineering and Management Sciences, 2016)
Development of the Science and practical application of the results created big changes in the nontradicional areas too. The „Health industry” was developed. The results of the physics, chemistry, biology and mikroelektronics etc. helped to develop some new methods of diagnosis, operation etc. The „money industry” was developed too. Our opinion is, that the most important cause of the economic crisis is a non regulated well of the „money industry”. The „knowledge industry” was developed too. The „knowledge industry” contains all level of teaching and Research + Development + Innovation. Our analyze shows that the Innovation is the most important factor of the economic Development of Society. The new scientific results created big changes in area of the Management. The „Management Science” was developed as an independent area. Some management specialists developed some management methods (eg. Value Analysis, Risk Management, TRIZ, Lean methods etc.) for efficient allocation of sources.